Effect of intracanal cryotherapy on postoperative pain after endodontic treatment: systematic review with meta-analysis - Fernanda Garcias Hespanhol; Ludmila Silva Guimarães; Lívia Azeredo Alves Antunes; Leonardo Santos Antunes (Restorative Dentistry & Endodontics, 2022)
ObjectivesThis study aimed to evaluate the effectiveness of final irrigation with cold saline solution after endodontic treatment compared with saline solution at room temperature against postoperative pain following endodontic treatment.Materials and MethodsA broad search was performed in the PubMed, Web of Science, Scopus, Cochrane Library, Virtual Health Library (LILACS), and Grey Literature databases. Two independent reviewers performed data extraction, risk of bias using the Cochrane methodology, and certainty of evidence using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach.ResultsEight studies were included in qualitative synthesis. Intracanal cryotherapy favored the reduction of postoperative pain in the systematic review. Four studies were included in meta-analyses. The meta-analysis showed that intracanal cryotherapy reduced postoperative pain in teeth with symptomatic apical periodontitis (SAP) at 24 hours. There was no association between intracanal cryotherapy and control (room temperature) groups in teeth with normal periapical tissue with respect to postoperative pain at 24 hours and 48 hours.ConclusionsIntracanal cryotherapy was effective in reducing postoperative pain after endodontic treatment in teeth with SAP.